2018
DOI: 10.1093/ageing/afy105
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin intake is associated with risk of frailty in older adults

Abstract: a lower intake of vitamins B6, C, E and folates was associated with a higher risk of frailty. Not meeting RDAs for vitamins was also strongly associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…The aim of their analysis was to assess the association between dietary vitamin intake and the development of frailty in older adults 4. A total of 1643 community-dwelling participants aged 65 years or older were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of their analysis was to assess the association between dietary vitamin intake and the development of frailty in older adults 4. A total of 1643 community-dwelling participants aged 65 years or older were included.…”
Section: Methodsmentioning
confidence: 99%
“…The focus of analysis for Balboa-Castillo et al 4 was dietary intake of 10 key vitamins, including vitamins A, B 6 , B 12 , C, D, E, thiamine, riboflavin, niacin and folate, in those aged >65 years and their association with the development of frailty. Although not all of the data analysed showed statistically significant results, the authors note that, overall, those who failed to meet the recommended daily intake of five or more vitamins were at increased risk of frailty 4. It is suggested that vitamin intake could be easily ascertained with a simple dietary interview.…”
Section: Commentarymentioning
confidence: 99%
“…In addition, the not-frail group had a higher proportion of individuals living in urban areas. In terms of comorbidities, the frail group had higher proportion of individuals with dementia, OA, [ 31 ] RA, and osteoporosis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a 3.5-year follow-up, the lower intake of vitamins B6, C, E, and folates was associated with a higher risk of frailty, but B12 was not correlated. [ 31 ] Swart et al evaluated the effect of a 2-year daily oral supplementation of 500 ug of B12 in the intervention group (1454 patients) and control group (1452 patients). Physical performance including gait speed, HGS, and fall risk were also measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation